Solubility enhancement of nimodipine through preparation of Soluplus® dispersions - Rawda Yaseen AlSheyyab, Rana Mohammad Obaidat, Yara Radi Altall, Rana Talal Abuhuwaij, Rand Radwan Ghanma, Anoud Sameer Ailabouni, Hadeia Ahmad Mashaqbeh, Shayma Al-Haj (Journal of Applied Pharmaceutical Science, 2019)
The present work aims to enhance the water solubility of nimodipine, a hydrophobic drug, using a solid dispersion (SD) technique. Soluplus® as a novel hydrophilic polymeric carrier was used. Nimodipine-Soluplus® SDs (1:10) were prepared by impregnation technique using supercritical fluid technology (SCF) and compared with the ones which were prepared by conventional hot-melt (HM) method. The solubility and the in vitro release study of the raw drug, solid dispersions, and the corresponding physical mixtures were characterized and compared. The prepared SD by SCF technology showed 77-fold increase in nimodipine solubility, in comparison to 48-fold increase when prepared by HM and 7.7-fold when physically mixed. Moreover, they showed the highest percentage of nimodipine cumulative release within the studied period. The results were confirmed the amorphous transfer of the drug into the polymer matrix which was assured by the powder X-ray diffraction and the thermal analysis. In addition to the hydrogen bond formation between nimodipine and Soluplus®, which was evident in the FTIR spectra; A weakening of peak related to nimodipine N–H stretching and C=O of the ester group. Nimodipine solid dispersion with Soluplus® using the SCF technology might represent a promising formulation for nimodipine to enhance its oral bioavailability.
Keywords: Nimodipine, solid-dispersion, Soluplus®, supercritical fluid technology.